KEWAJIBAN PENGUSAHA MENYEDIAKAN ANGKUTAN ANTAR JEMPUT BAGI PEKERJA/BURUH PEREMPUAN YANG BERANGKAT DAN PULANG PADA MALAM HARI DI BALI SAFARI AND MARINE PARK - I Made Udiana; I Ketut Westra; Ni Ketut Sri Utari (University of Udayana, 2015)
This study examined the obligations of entrepreneur as stated in the regulations minister. Byusing normative method, this study showed the obligations of the entrepreneur in accordancewith the laws and regulations governing between entrepreneurs and workers. By taking thecase study of Bali Safari and Marine Park, which is located in Gianyar, Bali, it showedthe significance of regulatory policies, the accompanying rights and obligations that wasinherent in industrial relations.